Development and Validation of a KAP Scale on Deworming Practices in Captive Asian Elephants, Assam - Phukan, Nikita; Pathak, Pallabi; Boro, Prashanta K.; Bordoloi, Gautam; Bhattacharjee, Kanta; Das, Gauranga; Hazarika, Snigdha; Borah, Biju (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during May–June, 2025 at the Dihing Patkai landscape of Assam on the development and validation of an Elephant Deworming KAP Scale involved in the care of captive Asian elephants (Elephas maximus). An initial pool of 42 items was generated through literature review, field observation, and expert consultation. Following content validation by 10 experts, 30 items (10 each for knowledge, attitude, and perception) were retained, all achieving a Scale Content Validity Index/Average (S-CVI/Ave) above 0.90. Knowledge items, scored on a 3-point scale, showed acceptable difficulty (p=0.43–0.73) and discrimination (r>0.30) indices, with three items flagged for refinement. Attitude and perception items, measured on a 5-point Likert scale with both positive and negative statements, demonstrated high internal consistency (Cronbach’s Alpha = 0.90 and 0.89, respectively). Pretesting and pilot testing were conducted with 20 elephant caregivers to ensure the tool’s clarity and usability. Pilot testing revealed moderate levels of knowledge (56.83%), attitude (63.20%), and perception (61.00%), which resulted in an overall moderate KAP score of 60.88%. These results indicated that, elephant handlers possessed a moderate degree of awareness and attitudes toward deworming practices. Nonetheless, the findings underscored the need for targeted educational interventions to further improve knowledge and perception levels. The validated KAP scale demonstrated strong reliability and was deemed a suitable instrument for future behavioural assessments and program evaluations aimed at enhancing elephant health management in similar contexts.